Personalisation: Developing or Destroying Customer Relations? - Fernandez, Sarah Kathryn (2008)
It is an universally accepted fact that the improvements in technology, and therefore communication, has allowed international business to thrive. This is especially true with regards to the Internet which offers lower overheads than a physical store as well as making products accessible throughout the globe: or if not accessible at least allows customers to become aware of what is on offer on the other side of the world. Websites such as uSwitch.com allow consumers to find the best deal for their needs when they are searching for a particular product, but increasingly the online shopping network is looking to increase profits for companies, and this is often done by encouraging consumers to interact with their screens be it from customised first name greetings to product recommendations to encouraging active participation in the creation and running of a website, the Internet is becoming more personalised in order to lure customers in. Even in the early stages, this has been somewhat effective, but is online personalisation truly beneficial to consumers? Many academics have already highlighted the issue of privacy with regards to personalisation: having to input information such as age, postcodes and email addresses allows companies to gather a multitude of information about consumers which can be disconcerting the prime concern being where this information is stored and who has access to it. These issues have already been discussed in detail (Chellappa and Sin, 2005; Volokh, 2000), but little has been done to confirm the overall reaction of consumers to companies' efforts to personalise their services in order to make their customers seem valued and understood. Are consumers motivated to personalise? Is the personalisation process beneficial to customer relationship management, or is it an annoyance which customers would rather do without? Is living in a world of virtual reality impacting on consumers in a negative fashion? And how likely is it that consumers will eventually grow to be co-producers?